STRATEGI PARENTING DIGITAL DALAM MENUMBUHKAN PERKEMBANGAN SOCIAL EMOSIONAL LEARNING (SEL) BAGI ANAK USIA DINI DI TKS MAYANG WANGI - Nuraini; Muslim; Abdul Haris (STKIP Subang, 2026)
The development of digital technology has become an integral part of young children’s lives. The increasing use of digital devices presents both opportunities and challenges for parents in supporting their children’s growth and development, particularly in the area of Social Emotional Learning (SEL). A lack of guidance in the use of technology has the potential to hinder the development of children’s social and emotional skills. Therefore, digital parenting strategies are needed to guide the positive use of technology in a way that aligns with children’s developmental needs. This study aims to describe digital parenting strategies for fostering Social-Emotional Learning (SEL) in young children at TKS Mayang Wangi. The study employed a qualitative approach, with data sources consisting of the school principal, teachers, and parents. Data were collected through observation, in-depth interviews, and documentation, and were subsequently analyzed through data reduction, data presentation, and drawing conclusions. The research findings show that digital parenting strategies at the Mayang Wangi Childcare Center are implemented through the enforcement of rules regarding device use, active supervision when children access digital devices, fostering positive communication between parents and children, and the use of educational digital media that conveys social and emotional values. Parents actively guide their children in selecting appropriate content, engage them in discussions about the content of what they watch, and help them understand the various emotions and social behaviors depicted in digital media. Additionally, empathy and social awareness are fostered through educational content that teaches the values of sharing, respecting others, and cooperating. The success of this strategy is supported by collaboration between schools and parents in monitoring children’s digital activities. Research findings indicate that consistent digital parenting can support the development of emotional recognition, self-control, communication, social interaction, and empathy toward others in early childhood.